A stilbazolium dye-based chromogenic and red-fluorescent probe for recognition of 2, 4, 6-trinitrophenol in water. (17th June 2020) - Dhiman, Sukhvinder; Kumar, Gulshan; Luxami, Vijay; Singh, Prabhpreet; Kumar, Subodh
Abstract : Probe DMAS-DP in water shows highly selective decrease in absorbance (475 nm) and fluorescence intensity (615 nm) with 2, 4, 6-trinitrophenol and colour change from red to yellow (visible light) and red fluorescent to black (365 nm light). Abstract : The nitroaromatic compounds (NACs) show absorption maxima below 400 nm and their determination using absorption and colour change requires probes with absorption beyond this region. Herein, we report a stilbazolium-based probe DMAS-DP, which undergoes aggregation in HEPES buffer with an absorption maximum at 475 nm (red colour) and these aggregates demonstrate a highly selective and sensitive change in their colour from red to light yellow with 2, 4, 6-trinitrophenol (TNP). The LOD for the determination of TNP is 100 pM, the lowest in the literature by using visible spectroscopy. Moreover, the aggregates of DMAS-DP emit fluorescence in the red region with a maximum at 615 nm (red under 365 nm light), which is quenched selectively by TNP. 2, 4, 6-Trinitrotoluene (TNT) and other NACs show insignificant changes in the visible spectrum of the aggregates of DMAS-DP, even when present in excess. Density functional theory (DFT)-based structure optimization studies reveal that the DMAS-DP attains the Z-conformation and its dimethylamino moieties form strong interaction with the protons of TNP and are responsible for the reduced force constant (color). This constitutes the first probe where a stilbazolium dye has been used for constructing a TNP-selective chromogenic and red-fluorescent probe.